Secreted cathepsin L-like peptidases are involved in the degradation of trapped antibodies on the surface of Echinostoma caproni - Cortés, Alba; Mikeš, Libor; Muñoz-Antolí, Carla; Álvarez-Izquierdo, María; Esteban, J Guillermo; Horák, Petr; Toledo, Rafael (Parasitology research, 2019)
Antibody trapping is a recently described strategy for immune evasion observed in the intestinal trematode Echinostoma caproni, which may aid to avoiding the host humoral response, thus facilitating parasite survival in the presence of high levels of local-specific antibodies. Parasite-derived peptidases carry out the degradation of trapped antibodies, being essential for this mechanism. Herein, we show that cathepsin-like cysteine endopeptidases are active in the excretory/secretory products (ESPs) of E. caproni and play an important role in the context of antibody trapping. Cysteine endopeptidase activity was detected in the ESPs of E. caproni adults. The affinity probe DCG-04 distinguished a cysteine peptidase band in ESPs, which was specifically recognized by an anti-cathepsin L heterologous antibody. The same antibody localized this protein in the gut and syncytial tegument of adult worms. Studies with cultured parasites showed that in vivo-bound antibodies are removed from the parasite surface in the absence of peptidase inhibitors, while addition of cathepsin L inhibitor prevented their degradation. These results indicate that cathepsin L-like peptidases are involved in the degradation of surface-trapped antibodies and suggest that cysteine peptidases are not only crucial for tissue-invading trematodes, but they can be equally relevant at the parasite-host interface in gut-dwelling flukes.
Keywords: echinostomióza; Echinostoma caproni; Cathepsin; cysteinové endopeptidasy; Antibodies, Protozoan; Cathepsin L; Cysteine peptidase; proteolýza; Cysteine Endopeptidases; Immune evasion; Proteolysis; Echinostoma; Immune Evasion; zvířata; imunitní únik; protilátky protozoální; Echinostomiasis; Trematode; kathepsin L; Antibody; Animals